Functional Outcomes: One Year after a Cardiac Arrest - Raina, Ketki D. (Biomed Res Int, 2015)
Objective. The study aim was to characterize the time-course of recovery in impairments, activity limitations, participation restrictions, disability, and quality of life during the first year after cardiac arrest. Secondarily, the study described the associations between the instruments used to measure each of these domains. Methods. Measures of global disability (Cerebral Performance Category, CPC, Modified Rankin Scale, mRS), quality of life, activity limitations, participation restrictions, and affective and cognitive impairments were administered to 29 participants 1, 6, and 12 months after cardiac arrest. Results. Global measures of disability indicated recovery between one month and one year after cardiac arrest (mean CPC: 2.1 versus 1.69,  P < 0.05; mean mRS: 2.55 versus 1.83, P < 0.05). While global measures of disability were moderately associated with participation, they were poorly associated with other measures. The cohort endorsed depressive symptomatology throughout the year but did not have detectable cognitive impairment. Conclusions. Recovery from cardiac arrest is multifaceted and recovery continues for months depending upon the measures being used. Measures of global disability, reintegration into the community, and quality of life yield different information. Future clinical trials should include a combination of measures to yield the most complete representation of recovery after cardiac arrest.